Analysis on Data Uncertainty of HLW Disposal Process. Issue 2 (February 2019) - Ma, Jiayi; Huang, Shutao
Abstract: HLW disposal process includes many uncertainties, such as scenario uncertainties, model uncertainties and data and parameter uncertainties and so on. However, the uncertainty of data is the source of all other uncertainties. Regarding addressing the data uncertainties in HLW disposal process, the paper focus on analyzing the concrete performing form of spatial uncertainties, and figure out the reason of producing the data uncertainties. Meanwhile, the paper points out the influence of the uncertainties and the solution of addressing and eliminating the spatial uncertainties.